Cysteamine hydrochloride, a transglutaminase2 inhibitor as therapeutic potential for oral submucous fibrosis - Basetty N Rajarathnam; Nagaraju Rakesh; Anita Murali; J Anbu; M L Asha (Wolters Kluwer Medknow Publications, 2023)
Background: Submucous fibrosis (SMF) was recognized as a definitive lesion by Schwartz who described it as a fibrosing condition in 1952 and due to its predilection for afflicting multiple sites in the oral cavity the disorder was listed as a "premalignant/precancerous condition". Tissue transglutaminase 2 (TG2) catalyzes the cross-linkage between glutamine (Gln) and lysine (Lys) side chains. Cysteamine by virtue of being a transglutaminase 2 substrate, acts as a competitive inhibitor of the other amine substrates of this enzyme. In-vitro studies have reported the existence of a correlation between TG2 and SMF. Aim: The present study was carried out to evaluate Transglutaminase2 (TG2) and its therapeutic intervention by cysteamine hydrochloride in SMF-affected Wistar rats. Methods: The present experimental study was carried out on male Wistar rats, in which arecoline was injected into the right buccal mucosa for induction of SMF, and levels of TG2 were estimated using ELISA. The drug was administered to disease-induced Wistar rats from the 91st day for inhibition of TG2 and the post-treatment levels of TG2 were evaluated by ELISA at three regular intervals (97th, 104th, 111th days). Results: The Animal model exhibited a successful induction of SMF similar to the histopathological features of human SMF. The levels of TG2 were significantly elevated in the experimental animals compared with the healthy animal group up on the induction of the disease process. On administration of cysteamine to the SMF-affected animals, TG2 levels significant reduction by the 111st day was observed. Conclusion: The results from this present study highlight the newer therapeutic option for SMF. Exploring the old drug cysteamine can be a significant forward step towards novel treatment strategies for the treatment of SMF.